If you want to multiply (2*x + 5) and (2*x - 5), you can do this using the following steps:
(2*x + 5) * (2*x - 5) = 4*x^2 - 10*x + 10*x - 25 = 4*x^2 - 25
The correct result is 4*x^2 - 25.
Answer:
7h+10
Step-by-step explanation:
Answer:
![\frac{4w {}^{8} }{9m {}^{4} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B4w%20%7B%7D%5E%7B8%7D%20%7D%7B9m%20%7B%7D%5E%7B4%7D%20%7D%20)
Step-by-step explanation:
separate with like terms
![\frac{4}{9} , \: \frac{w {}^{9} }{w} \: and \: \: \frac{m {}^{5} }{m {}^{9} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B9%7D%20%2C%20%5C%3A%20%20%5Cfrac%7Bw%20%7B%7D%5E%7B9%7D%20%7D%7Bw%7D%20%20%5C%3A%20and%20%5C%3A%20%5C%3A%20%20%5Cfrac%7Bm%20%7B%7D%5E%7B5%7D%20%7D%7Bm%20%7B%7D%5E%7B9%7D%20%7D%20)
the first fraction can be left alone as it can't be simplified any further
the second fraction can be written as w⁹ ÷ w¹ , when the bases are the same and division is involved subtract the powers: 9 - 1 = 8, so it's simplified to w⁸
the third fraction can be written as m⁵ ÷ m⁹, subtract the powers: 5 - 9 = -4, so it's simplified to m⁻⁴
![{m}^{ - 4} = \frac{1}{m {}^{4} }](https://tex.z-dn.net/?f=%20%7Bm%7D%5E%7B%20-%204%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7Bm%20%7B%7D%5E%7B4%7D%20%7D%20)
putting it together:
![\frac{4w {}^{8} }{9m {}^{4} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B4w%20%7B%7D%5E%7B8%7D%20%7D%7B9m%20%7B%7D%5E%7B4%7D%20%7D%20)
Cut 25 with 5
5x3 = 15
15 = 15